2011
DOI: 10.1155/2011/486756
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case Report of Extensive Polyostotic Gorham's Disappearing Bone Disease Involving the Upper Extremity

Abstract: Gorham's disease is a rare disorder involving the proliferation of endothelial channels resulting in resorption and disappearance of bone. An unusual case of polyostotic Gorham's disease affecting the scapula, humerus, radius, and ulna in a 39-year-old woman is described. The patient had extensive disease spreading across both the glenohumeral and humeroulnar joints. This is the first report of Gorham's disease spreading across multiple joints in the upper extremity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…[3][4][5] Even rarer is multicentric involvement crossing multiple joints, with only a single case documented so far. 7 We report a case of multicentric VBS crossing glenohumoral, arcomioclavicular and elbow joints, which to our knowledge is the second reported case of VBS crossing multiple joints of upper limb as well as the case involving highest number of joints.…”
Section: Introductionmentioning
confidence: 83%
“…[3][4][5] Even rarer is multicentric involvement crossing multiple joints, with only a single case documented so far. 7 We report a case of multicentric VBS crossing glenohumoral, arcomioclavicular and elbow joints, which to our knowledge is the second reported case of VBS crossing multiple joints of upper limb as well as the case involving highest number of joints.…”
Section: Introductionmentioning
confidence: 83%
“…Approximately 300 cases of GSD are reported in literature. A total of 40 cases of Shoulder GSD and only 23 cases of Humerus GSD have been reported in the literature [2,3]. Garbers et al reported a rare case of Gorham-Stout disease of both shoulders [4].…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that Gorham's disease has an unpredictable natural history, although many case reports tell of spontaneous resolution after 2 to 3 years. 4 Patients with distal disease that is not expanding, such as in the clavicle or humerus, can be observed with serial radiography. In the patient presented here, conservative treatment was instituted with ongoing physical therapy as tolerated and pain control with NSAIDs as needed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a predilection for intramembranously formed bone. 4 As of 2013, only 200 cases had been reported in the literature, and adequate epidemiological statistics are unreliable. The vast majority of the cases reported involve only a single bone.…”
mentioning
confidence: 99%
See 1 more Smart Citation